High marker density GWAS provides novel insights into the genomic architecture of terpene oil yield in Eucalyptus. Issue 3 (19th June 2019) - Kainer, David; Padovan, Amanda; Degenhardt, Joerg; Krause, Sandra; Mondal, Prodyut; Foley, William J.; Külheim, Carsten
Summary: Terpenoid‐based essential oils are economically important commodities, yet beyond their biosynthetic pathways, little is known about the genetic architecture of terpene oil yield from plants. Transport, storage, evaporative loss, transcriptional regulation and precursor competition may be important contributors to this complex trait. Here, we associate 2.39 million single nucleotide polymorphisms derived from shallow whole‐genome sequencing of 468 Eucalyptus polybractea individuals with 12 traits related to the overall terpene yield, eight direct measures of terpene concentration and four biomass‐related traits. Our results show that in addition to terpene biosynthesis, development of secretory cavities, where terpenes are both synthesized and stored, and transport of terpenes were important components of terpene yield. For sesquiterpene concentrations, the availability of precursors in the cytosol was important. Candidate terpene synthase genes for the production of 1, 8‐cineole and α‐pinene, and β‐pinene (which comprised > 80% of the total terpenes) were functionally characterized as a 1, 8‐cineole synthase and a β/α‐pinene synthase. Our results provide novel insights into the genomic architecture of terpene yield and we provide candidate genes for breeding or engineering of crops for biofuels or the production of industrially valuable terpenes.